Gender-bender: Perceptions of College Students in Tangerang on the Portrayal of Gender Roles in Popular Media - Juan Osbert Ethan Widjaya; Deborah Nauli Simorangkir (Universitas Multimedia Nusantara, 2023)
Media representation defines social reality by virtue of meanings negotiated through symbols, creating symbolic boundaries that define identities, one of which is gender. Symbolic boundaries of gender have revolved around the roles of masculinity and femininity, much of which were socialized by the media. Dove Cameron's